Sediment Transport A Geophysical Phenomenon - Gyr, Albert; Hoyer, Klaus (Fluid Mechanics and Its Applications, 2006)
A major part of this sediment transport representation closely follows the progress made in understanding the interactions between a turbulent flow and transportable solid particles. Introducing new aspects found in the research of turbulent flows, this book updates the theory of sediment transport, e. g. , using new representations for flow separations, and coherent structures thought to be relevant and confronts the problem that existent theories do not relate directly the relevant quantities involved in the physical processes. A review of the complex matter suggests that a closer cooperation between engineers and physicists would benefit the problem and our concept tries to acknowledge this fact. Having this in mind the book was organized in four parts. The engineer who is interested in predicting sediment transport will find the classical as well as statistical approaches in the first part (Chaps. 1-4). The second part (Chaps. 5-8) critically reviews the most problematic issues like rheology, turbulence, topological aspects of flow separations, vortical dynamics, and scaling parameters. This part is mainly addressed to the physicist interested in the geophysical aspects of river dynamics but will also support the engineers in their decision making process, when constructing a simulation scheme. The third part (Chaps. 9-11) presents the sediment transport using micromechanical principles, using new results from turbulence research and introducing flow separation as the main self-organization mechanism observed in the formation of bedforms.